2015
DOI: 10.1002/adsc.201401146
|View full text |Cite
|
Sign up to set email alerts
|

Monofluoromethylation of Tetrahydroisoquinolines by Visible‐light Induced Direct C(sp3)H Bond Activation

Abstract: A visible‐light photoredox‐catalyzed reaction of tetrahydroisoquinolines with β‐fluorinated gem‐diols results in the formation of C1‐monofluoromethylated tetrahydroisoquinolines via C(sp3)H bond activation. This protocol provides a new method to introduce a CF group with stable, easily‐prepared monofluorinated gem‐diol as CF source. A mechanistic investigation is presented based on control experiments.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In 2014, Zhu and co‐workers achieved the visible light‐induced difluoromethylation of tetrahydroisoquinolines with β,β‐difluorinated gem ‐diols as CF 2 source . As a continuation of their interest in visible light‐promoted C−H bond activation and in consideration of the importance of fluoro‐containing organic compounds, these authors reported the monofluoromethylation of tetrahydroisoquinolines with easily‐prepared trifluoromethyl β‐fluorinated gem ‐diols as CF source (Scheme ) …”
Section: C(sp3)−h Bond Functionalizationmentioning
confidence: 99%
“…In 2014, Zhu and co‐workers achieved the visible light‐induced difluoromethylation of tetrahydroisoquinolines with β,β‐difluorinated gem ‐diols as CF 2 source . As a continuation of their interest in visible light‐promoted C−H bond activation and in consideration of the importance of fluoro‐containing organic compounds, these authors reported the monofluoromethylation of tetrahydroisoquinolines with easily‐prepared trifluoromethyl β‐fluorinated gem ‐diols as CF source (Scheme ) …”
Section: C(sp3)−h Bond Functionalizationmentioning
confidence: 99%
“…It was shown that monofluoro enolates 21 can react with tetrahydroisoquinolines 60 under visible‐light photoredox catalysis conditions in the presence of a catalyst generated from RuCl 2 and 1,10‐phenanthroline (Scheme ) 52a. The additions take place at ambient temperature to afford products 62 with yields ranging from 42 to 88 %.…”
Section: Reactions Of Free Fluoro Enolates Generated In Situmentioning
confidence: 99%
“…Fu and co‐workers have reported the oxidative coupling of tetrahydroisoquinolines with trimethyl(trifluoromethyl)silane using rose bengal as the photocatalyst . Zhu and co‐workers have disclosed mild mono‐ and difluoromethylation of tetrahydroisoquinolines with in‐situ generated fluoroenolate from the corresponding β‐fluorinated gem ‐diols (Scheme a) b) .…”
Section: Introductionmentioning
confidence: 99%